Delivery of the p67 sporozoite antigen of Theileria parva by using recombinant Salmonella dublin: Secretion of the product enhances specific antibody responses in cattle - Gentschev, I.; Glaser, I.; Goebel, W.; McKeever, Declan J.; Musoke, A.J.; Heussler, V.T. (American Society for Microbiology, 1998)
The p67 sporozoite antigen of Theileria parva has been fused to the C-terminal secretion signal of Escherichia coli hemolysin and expressed in secreted form by attenuated Salmonella dublin areA strain SL5631. The recombinant p67 antigen was detected in the supernatant of transformed bacterial cultures. Immunization trials in cattle revealed that SL5631 secreting the antigen provoked a 10-fold-higher antibody response to p67 than recombinant SL5631 experessing but not secreting p67. Immunized calves were challenged with a 90 percent lethal dose of T. parva sporozoites and monitored for the development of infection. Two of three calves immunized intramuscularly with the p67-secreting SL5631 strain were found to be protected, whereas only one of three animals immunized with the nonsecreting p67-expressing SL5631 strain was protected. This is the first demonstration that complete eukaryotic antigens fused to the C-terminal portion of E. coli hemolysin can be exported from attenuated Salmonella strains and that such exported antigens can protect cattle against subsequent parasite challenge.